Composição e Estrutura da Comunidade Endoparasitária de Ageneiosusinermis(Linnaeus, 1766) (Siluriformes: Auchenipteridae) da planície de inundação do alto rio Paraná, Brasil - Pizani, Ana Paula Cirqueira Lucas (2013)
Among the most infected fish are vertebrates, this probably occurs by the peculiarities existing in the aquatic environment, which enables the access and penetration of pathogens become facilitated. Brazil, the largest country of the Neotropical region, is characterized by having numerous and voluminous bodies of water where a rich and diverse fish fauna known, which are parasitized by a large number of species belonging to many phyla lives. Little is known about the diversity of parasites present in these fish. The absence of studies related to the parasite ecology of Ageneiosusinermis associated with the hypothesis that the composition and structure of endoparasites of A. inermis suffer intrinsic and extrinsic interference of parasite-host-environment, enabled the realization of this work, which evaluated effects and described the component community endoparasites of 49 hosts collected in the floodplain of the upper Paraná River, between March 2010 and February 2013 Forty (81.63%) harbored at least one species of endoparasito, totaling 14 species four rate: Cestoda, Digenea, Nematoda and Acanthocephala, composed of both autogenic as allogenic species.